SISTEM INFORMASI PENGOLAHAN DATA PENDUDUK DI KELURAHAN PETAPAHAN BERBASIS WEB - Giska Yufani; Rimbun Siringoringo; Resianta Perangin-angin; Eva Julia G. Harianja (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2022)
In this modern era, developments in technology are very fast as in the present, there are in the government or private fields which are required to be followed or known to the way of information in all fields, especially in the field of computers or technology. The development of technology at this time is the result of technology that uses computers in order to process exact data in searching for data and can reduce errors or human errors in searching population data. Population data processing is a task within the Regency/City government, which is carried out starting from the main one, namely the kelurahan by recording population data. Processing data in various government places as needed so that they can process real, fast and precise information. The dependence of society on a technology continues to advance so that the level of information can improve in processing. So it is necessary to design an information system that can manage data in order to make it easier for employees to complete their work and can help residents get services faster and without requiring a lot of time.